A bio-sustainable approach for reducing Eucalyptus tree-caused agricultural ecosystem hazards employing Trichoderma bio-sustained spores and mycorrhizal networks - Kabir, Md. Golam; Wang, Yonglong; Abuhena, Md.; Azim, Md. Faisal; Al-Rashid, Jubair; Rasul, Noorain Munim; Mandal, Dipa; Maitra, Pulak (Frontiers in Microbiology, 2023)
The presence of the exotic Eucalyptus tree in crop-growing soil and the accumulation of its undecomposed leaves is a significant ecological hazard. The waxy coating on the leaves and the phenolic compounds takes a long time to break down under normal conditions. It is necessary to explore various fungi that can degrade these leaves for an eco-friendly solution to this problem. In this study, spores of nine native Trichoderma strains were produced on wheat agar using a lactic acid-induced sporulation strategy (LAISS). Trichoderma biosustained spores and Serendipita indica (SI) spores were applied to a rice field with accumulated Eucalyptus leaves under continuous ponding (CP) and alternate flooding and wetting conditions (AFW). Among the strains, TI04 (Trichoderma viride) and TI15 (Trichoderma citrinoviride) showed faster (5 days) and massive sporulation (1.06–1.38 × 1011 CFU/g) in LAISS. In vitro, TI04 and TI15 biosustained on Eucalyptus leaves and improved rice seedling growth and SI infection under greenhouse conditions. In the rice-field experiment, Trichoderma-treatment had a threefold yield (percentage) increase from control, with TI04 (CP) increasing the yield by 30.79, TI04 (AFW) by 29.45, TI15 (CP) by 32.72, and TI15 (AFW) rising by 31.91. Remarkably, unfilled grain yield significantly decreased in all the Trichoderma treatments. Under AFW conditions, TI04 and TI15 showed a higher pH increase. Furthermore, TI04 and TI15 under AFW had higher water productivity (t ha−1 cm−1) of 0.0763 and 0.0791, respectively, and the highest rates (percentage) of SI colonization of 86.36 and 83.16, respectively. According to the findings, LAISS-produced Trichoderma spores can be applied to break down persistent wastes and restore agricultural ecosystems through increased mycorrhizae networking.